30 jaar Ra : Radiant - Turner, Ralph; den Besten, Liesbeth; Boot, Marjan (Amsterdam : Galerie Ra, 2006)
Bakker, Gijs ; Bauer, Ela ; Bauhuis, Peter ; Blickman, Sylvia ; Blyfield, Julie ; Brennand-Wood, Michael ; Bronger, Sigurd ; Buhs, Bussi ; Chan, Kai ; Chang, Peter ; Dahm, Johanna et al.
A look back at 30 years of Galerie Ra in essays by Ralph Turner, Liesbeth den Besten and Marjan Boot. With illustrations of past and recent work by 50 gallery artists. (from publisher)
boek